Disseminated nocardiosis in a patient on infliximab and methylprednisolone for treatment-resistant Sweet's syndrome - Elizabeth R Drone; Allison L McCrory; Natalie Lane; Katherine Fiala (Wolters Kluwer Medknow Publications, 2014)
A 62-year-old white man with a 10-year history of treatment-refractory Sweet's syndrome was admitted to the hospital with the onset of purpuric lesions. Methylprednisolone and infliximab were administered. Our patient developed disseminated Nocardia infection and eventually succumbed. Opportunistic infections such as Nocardia have been associated with infliximab and other tumour necrosis factor (TNF)-α inhibitors. The astute clinician should be aware of the risk of rare opportunistic infections, particularly in patients on TNF-α inhibitors and systemic corticosteroids.